Effect of alkali (K/Na) metal vapor on the metallurgical properties of coke in CO2–O2–N2 mixed atmosphere. (15th October 2022) - Wang, Meichen; Wei, Guangsheng; Yang, Shufeng; Zhu, Rong; Yang, Lingzhi
Abstract: The mixed injection of CO2 and O2 in blast furnace is a novel method. The effect of alkali metal vapor on coke structure was studied by gas phase adsorption method. XRD, Raman and other characterization methods showed that K/Na metal vapor reacted with carbon matrix to form new minerals, which destroyed the original dense aromatic ring structure of metallurgical coke and reduced the high-temperature properties of metallurgical coke. In this work, the influence mechanism of alkali metals on coke in blast furnace in CO2 –O2 –N2 mixed atmosphere was studied by thermogravimetric analysis. The dynamic analysis results show that when the heating rate is 5 K min −1, the deviation value of VM is only 0.64%, and the corresponding urcm is 1.4%. Other experimental results show similar results, indicating that the product model (VM) has the best simulation effect on the reaction process of metallurgical coke. Graphical abstract: Image 1 Highlights: The influence mechanism of alkali metals on the metallurgical properties of blast furnace coke was systematically studied. It is innovative to study the reaction characteristics of coke in CO2 –O2 –N2 atmosphere. The dual effects of CO2 gas and alkali metal on coke reaction were studied. The reaction was described by molecular dynamics.